Short dental implants versus standard dental implants placed in the posterior jaws: A systematic review and meta-analysis - Lemos, Cleidiel Aparecido Araujo [UNESP]; Ferro-Alves, Marcio Luiz [UNESP]; Okamoto, Roberta [UNESP]; Mendonça, Marcos Rogério de [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2016)
Objective The purpose of the present systematic review and meta-analysis was to compare short implants (equal or less than 8 mm) versus standard implants (larger than 8 mm) placed in posterior regions of maxilla and mandible, evaluating survival rates of implants, marginal bone loss, complications and prosthesis failures. Data This review has been registered at PROSPERO under the number CRD42015016588. Main search terms were used in combination: dental implant, short implant, short dental implants, short dental implants posterior, short dental implants maxilla, and short dental implants mandible. Source An electronic search for data published up until September/2015 was undertaken using the PubMed/Medline, Embase and The Cochrane Library databases. Study selection Eligibility criteria included clinical human studies, randomized controlled trials and/or prospective studies, which evaluated short implants in comparison to standard implants in the same study. Conclusion The search identified 1460 references, after inclusion criteria 13 studies were assessed for eligibility. A total of 1269 patients, who had received a total of 2631 dental implants. The results showed that there was no significant difference of implants survival (P =.24; RR:1.35; CI: 0.82-2.22), marginal bone loss (P =.06; MD: -0.20; CI: -0.41 to 0.00), complications (P =.08; RR:0.54; CI: 0.27-1.09) and prosthesis failures (P =.92; RR:0.96; CI: 0.44-2.09). Short implants are considered a predictable treatment for posterior jaws. However, short implants with length less than 8 mm (4-7 mm) should be used with caution because they present greater risks to failures compared to standard implants. Clinical significance Short implants are frequently placed in the posterior area in order to avoid complementary surgical procedures. However, clinicians need to be aware that short implants with length less than 8 mm present greater risk of failures.
Keywords: Complications; Edentulous jaws partially; Marginal bone loss; Meta-analysis; Prosthesis failures